2019
DOI: 10.3390/en12132515
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Combined Solar-Assisted Heat Pump Heating System in Xi’an, China

Abstract: This study proposed a combined solar-assisted heat pump (SAHP) system that could operate in the serial mode or parallel mode. For this proposed system, a stable year-round operation could be achieved without the assistance of electric heating or low-temperature heat pump. By analyzing the heat balance equations, a correlation of the combined SAHP system for the two modes switched was obtained, which provided a theoretical basis for the optimal operation of this system. In addition, the performance of the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In Huan et al, [ 95 ] focus is devoted on the optimal strategy to be used in dual‐source heat pumps. The results from an experimental campaign indicate that the operation in serial or parallel mode is strongly influenced by ambient temperature and solar radiation within the same day and therefore there is the need to switch operating mode not only on seasonal basis but also within the same day.…”
Section: Solar‐coupled Vapor‐compression Heat Pumps For Space Heating...mentioning
confidence: 99%
“…In Huan et al, [ 95 ] focus is devoted on the optimal strategy to be used in dual‐source heat pumps. The results from an experimental campaign indicate that the operation in serial or parallel mode is strongly influenced by ambient temperature and solar radiation within the same day and therefore there is the need to switch operating mode not only on seasonal basis but also within the same day.…”
Section: Solar‐coupled Vapor‐compression Heat Pumps For Space Heating...mentioning
confidence: 99%
“…The results show that the average COP and exergetic COP are 6.14 and 1.49, respectively. Huan et al [11] proposed a hybrid system of solar heat pump that can work in series or parallel mode. The performance of the proposed system implemented in a university bathroom in Xi'an region.…”
Section: Introductionmentioning
confidence: 99%
“…In Huan, et al [15], a combined solar heat supply system with sequential and parallel modes was developed, and the results showed that in winter it is better to use a sequential mode, and in summer the parallel one is suitable. In the article Kong, et al [16], a numerical simulation of the solar heat supply system was developed, which confirmed the effectiveness of the system in freezing conditions.…”
Section: Introductionmentioning
confidence: 99%